2015
DOI: 10.1149/2.0411504jes
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of Electrochemical Flow Capacitors

Abstract: Electrochemical flow capacitors (EFCs) for grid-scale energy storage are a new technology that is beginning to receive interest. Prediction of the expected performance of such systems is important as modeling can be a useful avenue in the search for design improvements. Models based off of circuit analogues exist to predict EFC performance, but these suffer from deficiencies (e.g. a multitude of fitting constants that are required and the ability to analyze only one spatial direction at a time). In this paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 15 publications
1
32
0
Order By: Relevance
“…When using ferrous salts, solutions were made under a continuous nitrogen blanket and experiments were performed with the electrolyte under a continuous nitrogen purge to mitigate the air oxidation of ferrous to ferric iron. 37,38 All tests were conducted at room temperature (20)(21)(22)(23)(24)(25) • C). It was observed that when the volume fraction of the solid particles was above some critical concentration, there was no longer enough liquid in the slurry to fully wet all of the particles.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…When using ferrous salts, solutions were made under a continuous nitrogen blanket and experiments were performed with the electrolyte under a continuous nitrogen purge to mitigate the air oxidation of ferrous to ferric iron. 37,38 All tests were conducted at room temperature (20)(21)(22)(23)(24)(25) • C). It was observed that when the volume fraction of the solid particles was above some critical concentration, there was no longer enough liquid in the slurry to fully wet all of the particles.…”
Section: Methodsmentioning
confidence: 99%
“…At low frequency, the current response tends toward the steady-state, DC charging value that can be predicted using available models. 24,25 Thus, even in the situation with a separator present, the Nyquist plot still returns to the real axis at low frequency (instead of having its imaginary component diverge to negative infinity as in the stationary case). The evolution of the Nyquist plot at intermediate frequencies is difficult to ascertain though as the advection-diffusion of surface charge combined with sinusoidal perturbations requires time-dependent, two-dimensional numerical simulations of the governing slurry electrode equations.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…In our earlier work, 6 the capacitive Prandtl number of a typical candidate EFC slurry was shown to generally be a very large number; this suggests that the overpotential boundary layers grow much more slowly than the hydraulic boundary layers with respect to distance along the electrode. The challenges of achieving satisfactory current densities in an EFC is therefore similar to the challenges encountered in heat transfer into high Prandtl number fluids -possible remedies of which include designs that break up the overpotential boundary layers or induce turbulence.…”
Section: Mathematical Modelmentioning
confidence: 91%
“…Research efforts have pursued new materials, flow cell designs, surface modification, and mathematical modeling. 42,44,92,[99][100][101][102] More detailed discussion on the current status and research perspectives for supercapacitors and EFCs can be found in these recent reviews. 29,40,45,46,103,104 Capacitive water deionization is another application where solid suspensions have been coupled into a system with electrodes and electrical potential driving forces.…”
Section: Solid Suspensions For Capacitive and Electrochemical Applmentioning
confidence: 99%